REPORT ON THE EXCAVATIONS AT MERQULY: THE 2009 SEASON. (17th March 2015) - Saber, Saber Ahmed; Rejeb, Zuhair; Altaweel, Mark
Abstract : The site of Merquly is located in a mountain pass c . 40 km north-west of Slemani (Sulaimaniyah), Iraq. Excavation at the site in 2009 revealed a fortified structure whose rooms at multiple elevations reflect a terraced structure adapted to the steep landscape contours of its setting. Both architectural preservation and quantity of finds were relatively limited; however, despite the nearby presence of a prominent Parthian period rock relief, ceramics suggest a later Sasanian date for the site. The authors discuss the 2009 season's results, and consider possible parallels for the preserved architecture, although further work is needed to securely date and characterize the site.